The effects of ketogenic diet on the outcomes of polycystic ovary syndrome: A systematic review on clinical trials - Haniyeh Lorzadeh Amin; Morvarid Noormohammadi; Ghazaleh Eslamian (Mashhad University of Medical Sciences, 2022)
Introduction: Polycystic ovary syndrome is a major cause of anovulation and infertility in women that is associated with chronic diseases such as obesity, insulin resistance, diabetes, cardiovascular disease, and fatty liver disease. This systematic review was performed aimed to determine the effects of ketogenic diet on the outcomes of polycystic ovary syndrome.Methods: In this systematic review, the keywords of "polycystic ovary syndrome", "ketogenic diet", "low carbohydrate diet", and "clinical trials" were searched in databases of Medline, PubMed, Science Direct, Magiran, ISD, ISC and Cochrane in English and Persian language without time restrictions. Then, the articles relevant to the study's aim were reviewed.Results: In this research, 4 studies were examined. The results showed that following a ketogenic diet in patients with polycystic ovary syndrome may reduce the risk of cardiovascular diseases in these patients by lowering weight and body mass index, blood pressure, serum total cholesterol, and triglycerides.Conclusion: Long-term adherence to a ketogenic diet may result in weight loss, improved insulin resistance, and serum lipid profile disorders in patients with polycystic ovary syndrome. Clinical trials are suggested to evaluate the effects of ketogenic diet on these metabolic and endocrine factors in PCOS women.